Foxp3 Protein Stability Is Regulated by Cyclin-dependent Kinase 2 - Morawski, Peter A.; Mehra, Parul; Chen, Chunxia; Bhatti, Tricia; Wells, Andrew D. (The Journal of biological chemistry, 2013)
Foxp3 is a transcription factor required for the development of regulatory T cells (Treg). Mice and humans with a loss of Foxp3 function suffer from uncontrolled autoimmunity and inflammatory disease. Expression of Foxp3 is necessary for the anti-inflammatory capacity of Treg, but whether Foxp3 activity is further subject to regulation by extracellular signals is unclear. The primary structure of Foxp3 contains four cyclin-dependent kinase (CDK) motifs (Ser/Thr-Pro) within the N-terminal repressor domain, and we show that CDK2 can partner with cyclin E to phosphorylate Foxp3 at these sites. Consistent with our previous demonstration that CDK2 negatively regulates Treg function, we find that mutation of the serine or threonine at each CDK motif to alanine (S/T→A) results in enhanced Foxp3 protein stability in CD4+ T cells. T cells expressing the S/T→A mutant of Foxp3 showed enhanced induction (e.g. CD25) and repression (e.g. IL2) of canonical Foxp3-responsive genes, exhibited an increased capacity to suppress conventional T cell proliferation in vitro, and were highly effective at ameliorating colitis in an in vivo model of inflammatory bowel disease. These results indicate that CDK2 negatively regulates the stability and activity of Foxp3 and implicate CDK-coupled receptor signal transduction in the control of regulatory T cell function and stability. Background: Foxp3 post-translational regulation remains unclear. Results: Foxp3 is phosphorylated by cyclin-dependent kinase 2 (CDK2) and has increased stability and function without its CDK motifs. Conclusion: CDK2 is a negative regulator of Foxp3 function. Significance: Understanding how Foxp3 is stabilized could lead to new therapeutic measures for autoimmunity and transplantation.